Mental State Examination and Its Procedures—Narrative Review of Brazilian Descriptive Psychopathology - Rocha Neto, Helio Gomes; Estellita-Lins, Carlos Eduardo; Lessa, José Luiz Martins; Cavalcanti, Maria Tavares (Frontiers in Psychiatry, 2019)
Background: Mental State Examination (MSE) is compared with physical examination as a reliable method of objective data investigation. There is a growing concern with psychiatric clinics, nosology, and reliability of diagnostic interview methods as a source of valid diagnostic strategy. Efforts to achieve an international diagnosis protocol have been unsuccessful or polemical. This paper focuses on psychopathology, MSE, and mental functions development within Brazilian psychiatry in the last decades. Methods: Searches, interviews and a narrative review were done looking for systematic ways to conduct MSE, mental functions, symptom clusters, orientations about data observation and records. Brazilian psychopathology textbooks were examined, provided they mean ways to access consolidated knowledge on medicine. Results: Sixteen textbooks were selected from 49 years span. Descriptive psychopathology with phenomenological orientation was the primary trend in the MSE. Concepts derived from different traditions, most lacking common terminology, suggest some divergence among authors. Recommendations for patient observation and how to collect objective data was clear, but MSE standardization efforts are vacant. A detailed description of mental functions abnormalities was the main MSE record strategy, without consensus about ways to summarize and record. Examination summary, mental strata turned into divided "mental functions," and MSE subsets were sound and frequent. Most authors considered the following mental functions: consciousness, perception, thought, memory, attention, orientation, and volition. Discussion: Psychiatric competence demands MSE proficiency. Official documents are not clear about performance and recording standards. Descriptive psychopathology seems to be MSE usual way to get and record data. A shift from detailed descriptive findings to an array of observed pathological elements described through a mental functions checklist was observed over time. Clinical practice and research guidelines should consider the development of reliable MSE practices; however, it might have been neglected by modern psychiatry/neuroscience through an excessive emphasis on interview protocols. Better MSE practices, and improvement of bedside skills in psychiatry are necessary and will depend on recovering psychopathological debates and semiological reasoning, probably allowing a return to phenomenology-oriented "observational" technics.